A method to distinguish harmonic frequencies and remove the harmonic effect in operational modal analysis of rotating structures. (December 2021) - Chen, Wei; Jin, Mengshi; Huang, Jiasheng; Chen, Yuanchang; Song, Hanwen
Highlights: Correlation functions of the system under broadband and harmonic excitations are deduced. A harmonic identification and removal method is proposed based on correlation functions. The proposed method is verified through experiments for a beam and a rotation blade. The case where harmonic frequency overlaps with the natural frequency is considered. Abstract: Operational modal analysis (OMA) is used to identify the modal parameters of a structure under operational conditions, which reflects the real boundary conditions and state-dependent parameters. For rotating structures under operational conditions, in addition to broadband excitations, the harmonic excitation is also present and even dominates the responses in some cases. Since only the responses are recorded in OMA, the first problem lies in separating the resonant frequencies from the harmonic excitation frequencies. Moreover, if the frequency of the harmonic excitation is close to, or coincides with a resonant frequency of the system, classical modal analysis procedures will fail to identify the modal parameters accurately. These issues are addressed in this paper and a method is presented for distinguishing harmonic frequencies and removing the harmonic effect using correlation functions of the responses. Firstly, the correlation functions are deduced for the system under the combination of broadband and harmonic excitations, yielding the sum of free decay response of the system and sinusoids with the same frequencies as the harmonic excitations. Then, the principle of the method is presented using a numerical study on a two degree-of-freedom system. Both the noise resistance and method comparison studies are conducted in the simulation case. Subsequently, the effectiveness of the method is demonstrated through experiments on a light-damped beam, where cases of different harmonic intensity and different harmonic frequencies are considered. Lastly, the proposed method is applied to a rotating blade to extract modal parameters in its operational state.